Attention Deficit Hyperactivity Disorder and Risk of Posttraumatic Stress and Related Disorders: A Prospective Longitudinal Evaluation in U.S. Army Soldiers. Issue 6 (21st November 2018) - Howlett, Jonathon R.; Campbell‐Sills, Laura; Jain, Sonia; Heeringa, Steven G.; Nock, Matthew K.; Sun, Xiaoying; Ursano, Robert J.; Stein, Murray B.
Abstract: Cross‐sectional associations between attention deficit hyperactivity disorder (ADHD) and posttraumatic stress disorder (PTSD) have been observed, but longitudinal studies assessing this association are lacking. This prospective study evaluated the association between predeployment ADHD and postdeployment PTSD among U.S. Army soldiers. Soldiers who deployed to Afghanistan were surveyed before deployment (T0) and approximately 1 month (T1), 3 months (T2), and 9 months (T3) after their return. Logistic regression was performed to estimate the association between predeployment ADHD and postdeployment (T2 or T3) PTSD among 4, 612 soldiers with data at all waves and no record of stimulant medication treatment during the study. To evaluate specificity of the ADHD–PTSD association, we examined associations among predeployment ADHD, postdeployment major depressive episode (MDE), generalized anxiety disorder (GAD), and suicidal ideation. Weighted prevalence of ADHD predeployment was 6.1% ( SE = 0.4%). Adjusting for other risk factors, predeployment ADHD was associated with risk of postdeployment PTSD, adjusted odds ratio ( AOR ) = 2.13, 95% CI [1.51, 3.00], p < .001, including incidence among soldiers with no predeployment history of PTSD, AOR = 2.50, 95% CI [1.69, 3.69], p < .001. ADHD was associated with postdeployment MDE, AOR = 2.80, 95% CI [2.01, 3.91], p < .001, and GAD, AOR = 3.04, 95% CI [2.10, 4.42], p < .001, but not suicidal ideation. Recognition of associations between predeployment ADHD and postdeployment PTSD, MDE, and GAD may inform targeted prevention efforts. Future research should examine whether treatment of ADHD is protective against PTSD and related disorders in trauma‐exposed individuals.